Wayfinding learning techniques and its challenges: a case study at malaysian association for the blind (MAB) - Nazatul Naquiah Abd Hamid; Wan Adilah Wan Adnan; Fariza Hanis Abdul Razak (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Navigating safely in the real environment especially in the outdoor setting requires a blind person to be equipped with the spatial knowledge and possess the skills in mobility and orientation. The aims of this study are to investigate the existing wayfinding learning techniques taught to blind people and to identify the challenges during the teaching and learning processes. A two days of observation during a mobility practical session was conducted at Malaysian Association for the Blind (MAB). The first objective was to explore the current techniques used by mobility instructor to teach visually impaired students for a wayfinding and second, to identify the challenges faced by the mobility instructor and the visually impaired students in the teaching and learning processes of wayfinding. The study discovered that the major problem faced by the mobility instructor was with the lack of teaching aids to describe a new environment to visually impaired students. This leads to the lack of time that caused the visually impaired students perceived insufficient information which was hard for them to construct the intended cognitive maps. From the findings, this paper concludes by discussing the recommendations primarily on the use of technology in addressing the problems identified in this study.